2014
DOI: 10.1080/1331677x.2014.952112
|View full text |Cite
|
Sign up to set email alerts
|

Life and non-life insurance demand: the different effects of influence factors in emerging countries from Europe and Asia

Abstract: Urbanisation, incomes and their distributions, and the population degree of education are relevant factors for the development of insurance sector. This study estimates the different effects of the previously mentioned factors for life and non-life sector. We used the econometrics of panel data on 17 emerging economies from Asia and Europe over a 10-year period. We showed that urbanisation influenced significantly the life insurance demand in Asia, but not in Europe. Also, education was found to be significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 31 publications
2
56
0
5
Order By: Relevance
“…From Table 4 we can learn that this research has shown that incomes do have a significant and positive impact on demand for life insurance, but much more than GDP. Many authors have shown in their researches that there is a significant and positive impact of incomes on demand for life insurance, such as Sen and Madheswaran (2013), Dragos (2014), Feyen et al (2011 and others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Table 4 we can learn that this research has shown that incomes do have a significant and positive impact on demand for life insurance, but much more than GDP. Many authors have shown in their researches that there is a significant and positive impact of incomes on demand for life insurance, such as Sen and Madheswaran (2013), Dragos (2014), Feyen et al (2011 and others.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggest that income, inflation, interest rate, and the youth dependency ratio are significant determinants of life insurance consumption. Dragos (2014) estimates that a significant impact on the development of both life and non-life insurance has the income and its distribution among population. Using econometrics of panel data for 17 countries in Asia and Central Eastern Europe in the period of 10 years, she proved that the income has a positive impact on demand for insurance in CEE countries, while it has no significant impact on developing Asian countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current empirical research on life insurance lapse is focused on developed countries [Renshaw and Haberman 1986;Kagraoka 2005;Milhaud, Loisel, and Maume-Deschamps 2010;Eling and Kiesenbauer 2013; Canadian Institute of Actuaries 2014]. Although the literature on factors influencing life insurance demand in emerging countries has been increasing [most recently studies are: Elango and Jones 2011;Śliwiński, Michalski, and Roszkiewicz 2013;Dragos 2014], according to our best knowledge, besides two papers on the general characteristics on life insurance lapse in India [Kumar 2009;Surana and Gaur 2013], there is no study of policyholder and insurance contract factors influencing the exercise of life insurance options in emerging life insurance markets. Since the emerging markets have specific insurance market features as well as economic, demographic and social characteristics, it is valuable to investigate if the determinants of the use of life insurance options in developed insurance markets could be confirmed in emerging markets as well.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the life insurance demand caused by changes in the gross domestic product (GDP) [5] can be expressed by the elasticity of the demand for life insurance. According to the relevant data of gross domestic product and life insurance income, the elasticity of life insurance premium income to GDP in the 2001-2015 years can be calculated.…”
Section: Analysis Of the Impact Of Gross Domestic Product On The Pmentioning
confidence: 99%